1998
DOI: 10.1128/jcm.36.3.721-726.1998
|View full text |Cite
|
Sign up to set email alerts
|

Immunosorbent Assay Based on Recombinant Hemagglutinin Protein Produced in a High-Efficiency Mammalian Expression System for Surveillance of Measles Immunity

Abstract: Recombinant hemagglutinin (H) protein of the measles virus (MV) was produced in mammalian cells with a high-yield expression system based on the Semliki Forest virus replicon. Crude membrane preparations of H protein-transfected BHK-21 cells were used to coat microtiter plates to measure specific immunoglobulin G antibodies in 228 serologically defined serum samples mainly from measles late-convalescent adults. The titers by the enzyme-linked immunosorbent assay for the H protein (H-ELISA) closely correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 50 publications
(71 reference statements)
0
8
0
1
Order By: Relevance
“…No false-negative serum was detected, and increases between paired sera were as significant as they were with MV-ELISA. In light of these results and the overall high sensitivity and specificity of H-ELISA for IgG (3,4), we conclude that this assay is as reliable for the diagnosis of measles in paired sera as an ELISA based on whole MV. Despite the longer persistence of maximal levels of IgM in MV-ELISA and the early waning of H-specific IgM, the initial time courses of H-and MV-specific IgGs are similar.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…No false-negative serum was detected, and increases between paired sera were as significant as they were with MV-ELISA. In light of these results and the overall high sensitivity and specificity of H-ELISA for IgG (3,4), we conclude that this assay is as reliable for the diagnosis of measles in paired sera as an ELISA based on whole MV. Despite the longer persistence of maximal levels of IgM in MV-ELISA and the early waning of H-specific IgM, the initial time courses of H-and MV-specific IgGs are similar.…”
Section: Discussionmentioning
confidence: 76%
“…The nucleoprotein has been described as a suitable antigen to detect specific IgG and IgM (16,38,39). More recently we have shown that recombinant hemagglutinin (H) protein produced in a high-yield mammalian expression system can be used for the surveillance of measles immunity in late convalescents (3) and in vaccinees (4). The high sensitivity and specificity of this assay was due to high levels of detectable H-specific IgG antibodies in both of these cohorts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The coding sequence corresponding to the measles virus hemagglutinin (MV-H) protein (Bouche et al, 1998a) was subcloned into the expression cassette of the pRTL2 vector at the NcoI-BamHI sites (Restrepo et al, 1990). In this vector, the MV-H sequence was under the control of the constitutively expressed cauliflower mosaic virus (CaMV) 35S promoter fused to the tobacco etch virus (TEV) 5 -untranslated region, a translational enhancer, and the CaMV 35S terminator (Odell et al, 1985;Pietrzak et al, 1986).…”
Section: Construction Of a Plant Expression Vectormentioning
confidence: 99%